User profiles for populist counter-media websites in Finland. Issue 1 (1st April 2019) - Noppari, Elina; Hiltunen, Ilmari; Ahva, Laura
This article examines the users of Finnish populist counter-media (PCM) websites with the aim of exploring their motives for consuming and engaging with populist online media content. The article is based on a qualitative analysis of 24 semi-structured, focused interviews. We conclude that consuming and engaging with populist counter-media content is typically motivated by scepticism and mistrust of legacy media journalism and aspirations of constructing and sharing representations and narratives that challenge those of the dominant public sphere. These efforts are often motivated by deeply held personal beliefs and political stances. Three user profiles are devised to illustrate different types of counter-media users: (1) system sceptics, who express all-encompassing societal mistrust; (2) agenda critics, who express politicised criticism towards media representations of selected themes; and (3) the casually discontent, who sporadically browse sites for alternative information and entertainment.